Comparing plasma reduction and thermal hydrogenation in oxygen deficient TiO2-x nanotubes for photoelectrochemical H2 production - Khorashadizade, Elham; Rahimi, Kourosh; Mohajernia, Shiva; Hejazi, Seyedsina; Naseri, Naimeh; Moradlou, Omran; Moshfegh, Alireza; Schmuki, Patrik (International Journal of Hydrogen Energy, 2024)
Considering the urgent need for green energy carriers, hydrogen became a promising substitute for fossil fuel production via sustainable approach. Therefore, developing efficient photocatalysts using solar energy is the main issue. Here, we report experimental and computational studies on nature and influence of oxygen vacancies in different atomic layers of defective TiO2-x nanotubes photocatalysts. Although there are several studies that opened a new avenue to understand how to fabricate suboxide TiO2-x, there is no any comparative study reported on two main oxygen reduction techniques yet: cold plasma treatment and thermal hydrogenation. Oxygen vacancies and Ti3+ species produced by plasma reduction in a mixed Ar/H2 (90/10) under pressure of 10−3 Torr efficiently increase charge carrier life time (at optimum 15 W power) resulting in higher H2 production rate and significant incident photon to current efficiency (60%) in comparison with point defects produced by hydrogenation treatment. Various techniques utilized to fabricate oxygen deficient TiO2-x can lead to the creation of defects in specific atomic layers within the crystal structure. Therefore, we develop an ab initio model of the oxygen vacancies' formation at different depths of TiO2 slabs to study the effect of defects’ position in the crystal lattice on electronic structure against energy levels of water splitting reaction. This research provides a new and deep insight for designing suboxide black TiO2-x for efficient photocatalytic reactions especially for green energy production and environmental remediation.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Cold plasma reduction; Defective TiO; Hydrogen evolution; Oxygen vacancy defects; Thermal hydrogenation; Water splitting